Reovirus: Effect of Noninfective Viral Components on Cellular Deoxyribonucleic Acid Synthesis - Hand, Roger (1973)
We determined the effects of noninfective reovirus components on cellular deoxyribonucleic acid (DNA) synthesis. Reovirus inactivated by ultraviolet light inhibited cellular DNA synthesis, whereas reovirus cores and empty capsids did not. Both cores and empty capsids were adsorbed to cells. Adenine-rich ribonucleic acid (RNA) from reovirus, adsorbed to cells in the presence of diethyl-aminoethyl-dextran, produced a partial inhibition of DNA synthesis. RNA was synthesized in the presence of actinomycin D after infection with ultraviolet light-irradiated reovirus, and this RNA synthesis was not due to multiplicity reactivation of virus infectivity. These data suggest that viral structural proteins do not inhibit DNA synthesis and that the inhibition produced by ultraviolet-irradiated virus may be mediated in part or in toto by a newly synthesized viral product.